Patterns of institutional change for sustainability in Central and Eastern European agriculture - Franz Gatzweiler (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2003)
In this paper, the author discusses two different beliefs of how institutional change towards sustainability in agriculture and environment works: the institutional view and the evolutionary view. Both perspectives are studied in the context of restructuring the agricultural sectors and rural environments in Central and Eastern European Countries (CEECs). The specific nature of the agri-environmental problem calls for specific institutions and may require a specific building process. Case study results are presented showing the effect of EU accession on institutional change towards sustainability in several CEECs. The results provide evidence that the quality of institutional change required for sustainability goes beyond the building of legislative frameworks and requires more time than was envisaged by the roadmap to accession. Finally, the paper explores the role of social and human capital stocks in rural areas of CEECs outlining a number of differences in environmental governance in the agricultural sectors between various CEECs.
Keywords: 330; Institutioneller Wandel; Systemtransformation; Übergangswirtschaft; Nachhaltige Entwicklung; Landwirtschaft; Osteuropa